ANALISIS KEBERLANJUTAN USAHATANI KOPI ARABIKA BAWAKARENG KECAMATAN SINJAI BARAT KABUPATEN SINJAI - Awaluddin Awaluddin; Nuraeni Nuraeni; Mais Ilsan (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2018)
Indonesian arabica coffee is now a special coffee and is the best type of coffee, with a distinctive aroma because it has a special market. Its potential development in Indonesia is still very open, especially with the shift of ordinary coffee consumers to specialty coffee. This study aims to analyze the sustainability of Bawakaraeng Arabica coffee farming. This research was conducted in Sinjai Barat Subdistrict, Sinjai Regency, which took place from May to August 2017. Sampling / respondents were conducted randomly as many as 60 farmers. The data obtained were analyzed using the Multidimensional Scaling (MDS) approach which was the development of the Raled SBH method. The results showed that the production and income of Bawakaraeng Arabica coffee farming was less profitable for farmers because income per month for arabica coffee (peco) was approximately Rp. 340,981 and for Arabica coffee (logs) income per month Rp. 439,618, this is far below the minimum wage (UMP) of South Sulawesi province of Rp. 2,435,625 per month. Development of Arabica Bawakaraeng coffee farming based on ecological dimensions, economic dimensions, socio-cultural dimensions, infrastructure and technology dimensions, unsustainable legal and institutional dimensions.